1979
DOI: 10.1111/j.1751-0813.1979.tb15855.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosis Dietetica, Nutritional Myopathy, Mulberry Heart Disease and Associated Hepatic Selenium Levels in Pigs

Abstract: SUMMARY: Outbreaks of Hepatosis Dietetica (HD), Nutritional Myopathy (NM) and Mulberry Heart Disease (MHD) in Western Australia are described. Hepatic selenium concentrations were low in pigs with HD and NM, but not with MHD. The mean hepatic selenium concentration in pigs unaffected with these conditions was 1.07 ± 0.12 ppm dry wt. Cereal grain grown in an area of Western Australia where HD and NM frequently occur was found to be low in selenium and the addition of 0.1 ppm selenium to pig rations appeared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…In one experimental study, tissue selenium concentration did not appear to be related to the incidence of MHD‐related lesions (Sharp et al., 1972b). In Western Australia, hepatic selenium concentrations were not low in pigs with MHD (Moir and Masters, 1979). In field cases, heart and kidney selenium concentrations were similar in pigs of either group, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In one experimental study, tissue selenium concentration did not appear to be related to the incidence of MHD‐related lesions (Sharp et al., 1972b). In Western Australia, hepatic selenium concentrations were not low in pigs with MHD (Moir and Masters, 1979). In field cases, heart and kidney selenium concentrations were similar in pigs of either group, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies of vitamin E result in a wide variety of pathological changes in animal tissues. The main manifestations in pigs of vitamin E deficiency and Se deficiency are dietetic microangiopathy or Mulberry heart disease, hepatosis dietetica, and nutritional myopathy (Moir & Masters, 1979). Death from vitamin E and Se deficiencies, which is most likely to be seen in weaned pigs, is sporadic but can reach 5-10% of the herd (Van Vleet & Kennedy, 1989).…”
Section: Lipid Peroxidation: Vitamin E Requirementmentioning
confidence: 99%
“…Death from vitamin E and Se deficiencies, which is most likely to be seen in weaned pigs, is sporadic but can reach 5-10% of the herd (Van Vleet & Kennedy, 1989). It is suggested that mulberry heart disease is particularly related to vitamin E deficiency (Moir & Masters, 1979;Rice & Kennedy, 1989).…”
Section: Lipid Peroxidation: Vitamin E Requirementmentioning
confidence: 99%
“…Vitamin E addition confirmed the particular function of the vitamin as a lipid antioxidant and should be taken into consideration when diets with high PUFA concentrations are fed. (Fink et al, 1967;Moir and Masters, 1979), nutritional muscular dystrophy (NMD) also referred to as white muscle disease is one main consequence of dietary Se deficiency which is typical for ruminants (Hoshino et al, 1989;Bostedt and Schramel, 1990;Kozat, 2007) and turkeys (Scott et al, 1967). According to the literature, Se is the most effective nutritive factor for preventing NMD of gizzard, heart and skeletal muscle in turkeys (Scott, 1966;Scott et al, 1967;.…”
Section: Discussionmentioning
confidence: 99%